Peranan raja dan bangsawan Melayu dalam mengembangkan Islam di Tanah Melayu abad-19: penilaian menurut siasah Syar’iyyah - Hasnan Kasan ,; Mohamad Taha, (Universiti Kebangsaan Malaysia, 2002)
In Islam, rulers are leaders who are requested by Allah to implement the Islamic syaria in the territories under their control. Different methods in implementing the syaria are permitted as long as the objective of protecting the people from evils is upheld. Another important aspect in implementing syaria is the teaching of syaria itself. With that in mind, this paper attempts to discuss the role of Malay rulers in Malay Peninsular in the implementation of Islamic syaria in their territories